Oxidase-Loaded Hydrogels for Versatile Potentiometric Metabolite Sensing - Walker, Nicole L. (Biosens Bioelectron, 2021)
Continuous monitoring of biological metabolites of interest necessitates sensors that are robust, versatile, miniaturizable, and reliable. Electrochemical biosensors have dominated the field of biosensors for decades due to their robust and inexpensive nature. Classically, these sensors use amperometric and voltammetric methods as the sensing modality. One of the greatest limitations with these methods is the dependence of the signal (current, i) on the electrode size, which can change with respect to time due to fouling. Here, we present open circuit potential, an electrochemical technique that is relatively insensitive to electrode size, as a reliable alternative to amperometric and voltammetric techniques for monitoring metabolites of interest. The sensor operates by trapping an oxidase enzyme in a chitosan hydrogel. The oxidase enzyme is required for metabolite specificity. When the oxidase enzyme meets its substrate, oxygen is consumed, and hydrogen peroxide is generated. Hydrogen peroxide generation dominates a half reaction at the platinum surface, resulting in a change in potential. Using the above criteria, we demonstrate the efficacy, long lifetime, sensitivity, and ease of fabrication of glucose sensors, and miniaturize the sensors from macro- to micro-electrodes. Additionally, we demonstrate the ease with which this platform can be extended to detect other analytes in the form of a galactose sensor. Our results set a foundation for the generalized use of potentiometric sensors for a broad range of metabolites and applications.